2021
DOI: 10.1111/1745-9125.12273
|View full text |Cite
|
Sign up to set email alerts
|

Changing routine activities and the decline of youth crime: A repeated cross‐sectional analysis of self‐reported delinquency in Sweden, 1999–2017*

Abstract: This study examines the declining crime trend among Swedish adolescents between 1999 and 2017 using data from eight repeated cross‐sectional waves of a nationally representative school survey (N = ca. 49,000). We examined to what extent changes in parental monitoring, school bonds, attitudes toward crime, routine activities, and binge drinking were related to the noticeable decline in youth crime. Multilevel modeling was employed for the analysis of temporal trends. We found strong empirical support for our hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 120 publications
0
22
0
Order By: Relevance
“…Today's youth seem to belong to a generally well-behaved generation as there are observations of declines in crime [34] and other risk behaviours [35] parallel to the declines in youth drinking. There are also reports of normalising non-drinking in this generation [36,37], with small or no differences seen between drinkers and non-drinkers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Today's youth seem to belong to a generally well-behaved generation as there are observations of declines in crime [34] and other risk behaviours [35] parallel to the declines in youth drinking. There are also reports of normalising non-drinking in this generation [36,37], with small or no differences seen between drinkers and non-drinkers [38].…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, there has also been a large decline in alcohol use among Swedish adolescents [ 22 , 23 ] and internationally [ 24 , 25 ]. Involvement in criminal behaviour has also declined among youth in Sweden during this period [ 26 ]. There are also reports of declines in risk behaviors in general among adolescents [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we have not included any measures of online activities. It is important for future research to examine and include measures of young people’s online activities (e.g., Bunders & Weerman, 2020), since a number of studies have shown that there has been a decline in levels of participation in offline unstructured activities over time (Baumer et al, 2021; Svensson & Oberwittler, 2021). Third, the measures used for both unstructured and structured activities could be developed further to include other types of activities, and also to look in more detail at the effects of participation in team and individual sporting activities respectively (e.g., Badura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%